Public Health Center and Community,Two Important Elements in New Normal - Diki Prayugo Wibowo; Siti Uswatun Hasanah; Rival Ferdiansyah (Jurnal Berkala Kesehatan, 2023)
During the COVID-19 pandemic, stimulate education and awareness of the importance of a healthy lifestyle. Public health centers are at the front line of dealing with health problems, during the COVID-19 pandemic. The role, duties, and functions of the public health center are becoming increasingly important. All handling efforts to subscribe by the public health center require support from community components, one of which is public knowledge, especially regarding the transmission and methods of preventing Covid-19. The purpose of this community service activity is to directly educate the public about the new normal and support the health center in implementing healthy lifestyle. This service activity was designed by visiting the public health centers and counseling the community in Kabupaten Bandung, as well as distributing masks, hand soap, and hand sanitizers. The Public health center and the community appreciate this activity. The community gets knowledge and assistance regarding clean and healthy living habits. Support for these two aspects is expected to be one way to stop the spread of the COVID-19 infection in Bandung Regency.